ISOLATION AND CHARACTERIZATION OF FUNGI AND MYCOTOXINS (DEOXYNIVALENOL AND ZARALENONE) IN FISH FEED FROM BAGHDAD CITY. - Abdual-shahid, Dalia K.; Abbas, Oday S.; Mohammed, Zahid E. (Diyala Agricultural Sciences Journal, 2013)
This research provides a brief review of approaches for the early detection of fungi and its metabolites in feedof fish from some Baghdad farms. During a mycological analysis of complete feed mixes(15 samples), a total of five genera of moulds were identified. Penicillium spp. was present in considerably more samples than any other genus 36.4%, followed by the genera Fusarium spp.24.5%. Other fungi from the genera Aspergillus spp. 20%, Mucor spp. 11.1% and Alternaria spp. 8% were represented in a smaller amount.The mycotoxinsdeoxynivalenol and zearalenone were detected. Deoxynivalenol was detected in 10 samples in the concentration range 0.25–2.5 mg/kg. Zaralenone were detected in 8 samples in the concentration range 0.2–5.0 mg/kg.Thesefindings indicate that there may be a risk for animal exposure to mycotoxins through the consumption of moldy infected feeds